2002
DOI: 10.1590/s0104-79302002000100004
|View full text |Cite
|
Sign up to set email alerts
|

SCORPION ANTIVENOM REVERSES METABOLIC, ELECTROCARDIOGRAPHIC, AND HORMONAL DISTURBANCES CAUSED BY THE INDIAN RED SCORPION Mesobuthus tamulus concanesis, Pocock ENVENOMATION

Abstract: Electrocardiographic (ECG) changes were induced in dogs by injection of scorpion venom from Mesobuthus tamulus concanesis, Pocock. Venom (3 mg/kg body weight) was given subcutaneously (SQ) while 10 ml of scorpion antivenom (SAV) was administered intravenously (IV) to experimental dogs. Group 1 received only the venom; Groups 2, 3, and 4 received SAV at 0, 30, and 60 min, respectively, following envenoming. Thick, ropy and profuse salivation; muscle fasciculation; clonus and tetany-like contractions; frequent u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…3) Sofer and Gueron reported high levels of SGOT, CPK, and CK-MB and suggested that these might account for the cardiovascular changes. The electrocardiographic, echocardiographic, radionuclide and ventriculography studies also showed an elevation of SGOT, CPK and CK-Mb ratio in scorpion sting victims [54] [55].…”
Section: Acute Myocarditis and Cardiac Enzymesmentioning
confidence: 83%
See 1 more Smart Citation
“…3) Sofer and Gueron reported high levels of SGOT, CPK, and CK-MB and suggested that these might account for the cardiovascular changes. The electrocardiographic, echocardiographic, radionuclide and ventriculography studies also showed an elevation of SGOT, CPK and CK-Mb ratio in scorpion sting victims [54] [55].…”
Section: Acute Myocarditis and Cardiac Enzymesmentioning
confidence: 83%
“…The leaked enzymes remain in the circulation until they are metabolically degraded. This could be the reason for an apparent and significant rise in the enzyme levels in envenoming, and for reversal of ECG and cardiac enzyme levels following the administration of Scorpion antivenom (SAV) to the envenomed animals [55] [56].…”
Section: Acute Myocarditis and Cardiac Enzymesmentioning
confidence: 99%